"How I Became a Better Teacher:" Expanding Assessment Practices Rooted in Ethical Ideals. Issue 4 (2nd October 2022) - Furman, Cara
ABSTRACT: How do we help teachers grow in accordance with their ethical ideals? Specifically, how do assessment practices fit within teachers' sense of themselves as caring and professional early childhood educators? I pursue these questions by drawing on a collaborative blog. In doing so, I offer portraits of novice early childhood teachers as ethical agents committed to care and professionalism. I showcase how daily appeals to the developmental approach and milestone tracking informed these teachers' professional ethics. I, then, describe how undergoing and reflecting upon alternative approaches to assessment served as a disruption, pushing the teachers to expand their conception of assessment to observe both who the child is alongside what they can do. In closing, I call for teacher education that teaches a range of assessment practices within a context that "confirms" the teachers' ethical ideals.